2012
DOI: 10.1002/pssb.201084217
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of strain retention and shape memory in main chain liquid crystalline networks

Abstract: Liquid crystalline networks (LCNs) are described in which there is anelasticity in strain recovery response (under zero load) after uniaxial tensile loading. This strain retention is shown as a function of time after release of load and is further characterized by thermal, X‐ray, and stress/strain experiments. It was found that, at temperatures in the smectic phase far below the isotropization temperature, this LCN film retains significant levels of strain when in the monodomain state. On free recovery (zero l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 28 publications
(47 reference statements)
1
23
0
Order By: Relevance
“…A specimen of ~25 mm length was elongated at a rate of 0.125 mm/s. These elastomers usually show significant strain retention and, after the formation of monodomains, nearly half of the strain is retained [20] as shown in Figure 6. The residual strain increases with the magnitude of the applied strain above 50%, i.e., λ = 1.5.…”
Section: Polydomain Smectic-c Main Chain Liquid Crystal Elastomersmentioning
confidence: 99%
See 4 more Smart Citations
“…A specimen of ~25 mm length was elongated at a rate of 0.125 mm/s. These elastomers usually show significant strain retention and, after the formation of monodomains, nearly half of the strain is retained [20] as shown in Figure 6. The residual strain increases with the magnitude of the applied strain above 50%, i.e., λ = 1.5.…”
Section: Polydomain Smectic-c Main Chain Liquid Crystal Elastomersmentioning
confidence: 99%
“…Polydomain smectic MCLCEs have been extensively studied [20,[60][61][62][63][64][65][66][67]. Sánchez-Ferrer et al [64] reported the polydomain to monodomain (P-M) transition caused by uniaxial strain in these materials.…”
Section: Polydomain Smectic-c Main Chain Liquid Crystal Elastomersmentioning
confidence: 99%
See 3 more Smart Citations